English Language Learning: Visual Arts to Improve The seventh Graders’ Vocabulary of UPTD SMP Negeri 2 Gunungsitoli Alo’oa - Robin Motani Daeli; Yasminar Amaerita Telaumbanua; Elwin Piarawan Zebua; Trisman Harefa (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
This study investigates the use of visual arts to enhance vocabulary mastery among seventh-grade students at UPTD SMP Negeri 2 Gunungsitoli Alo’oa. The problem identified is students’ limited vocabulary caused by monotonous, text-based teaching methods that reduce motivation and engagement in English learning. This Classroom Action Research (CAR) employed a qualitative approach over two cycles, each involving planning, action, observation, and reflection. Visual art media used included an animated video and a thematic image titled “Home Sweet Home,” both designed to present vocabulary contextually and engagingly. Data collection tools included observation sheets, field notes, and evaluation tests using multiple-choice questions with visual cues. The minimum passing criterion was set at 70%. Results showed improvement in students’ vocabulary mastery, with average scores increasing from 84.83 in Cycle I to 92.00 in Cycle II. Students displayed greater understanding, enthusiasm, and participation when learning with visual media. The integration of both video and image media proved more effective than using a single medium, helping students connect vocabulary to visual contexts. In conclusion, visual arts are effective tools for vocabulary instruction, enhancing comprehension, memory retention, and student motivation in English learning.